Biochar applied to soil under wastewater irrigation remained environmentally viable for the second season of potato cultivation. (15th January 2020) - Nzediegwu, Christopher; Prasher, Shiv; Elsayed, Eman; Dhiman, Jaskaran; Mawof, Ali; Patel, Ramanbhai
Abstract: The environmental effectiveness of plantain peel biochar in the second season of its application to soil was studied using outdoor lysimeters (0.45 m diameter x 1.0 m height) packed with sandy soil, cultivated with potatoes (Solanum tuberosum) and irrigated with wastewater. Biochar (1% w/w) was amended in the soil one-time in the first season. For two seasons, the biochar improved the soil properties, immobilized the heavy metals in the soil, and reduced their uptake by the crop. The CEC of the biochar-amended soil (WW + B) for example, as compared to the unamended treatment (WW–B), was significantly higher (p<0.05; >65%) for both seasons due to higher pH which controls the availability of cations in soils, influencing their CECs. The soil sampled in the second season showed accumulation of all the heavy metals in the topsoil, while only Zn, Pb and Fe moved to the 0.1 m depth. The Fourier transform infra-red spectra of the soil and soil-biochar mix were similar and suggested that oxygen-containing functional groups were partly responsible for binding the heavy metals. The heavy metals translocated to all the potato parts (flesh, peel, root, stem and leaves). The concentrations of the heavy metals in potato parts under freshwater were lower than those under wastewater irrigated condition. After the second season of being in the soil, biochar significantly reduced (p < 0.05) the concentrations of Cd, Cu, Cr, Pb and Zn in the edible flesh suggesting that biochar immobilized wastewater-laden heavy metals in soil and reduced their uptake in potatoes for at least two seasons. Graphical abstract: Image 1 Highlights: The environmental viability of biochar was tested for the 2nd season in soil. 5/6 heavy metals (Cd, Cr, Cu, Pb and Zn) were reduced by biochar in potato flesh. Soil properties (e.g., CEC) were constantly influenced in the biochar-mixed soil. Biochar barely influenced the intensity of soil functional groups.